Global prevalence of stillbirth among fetuses from twin pregnancies: a systematic review and meta-analysis - Salari, Nader; Beiromvand, Mahan; Abdollahi, Reza; Hemmati, Mahvan; Heidarian, Pegah; Hashemian, Kimia; Shohaimi, Shamarina; Mohammadi, Masoud (Springer Science and Business Media Deutschland GmbH, 2025)
Background: Evidence shows that twin pregnancy is associated with increased adverse outcomes, including stillbirth. The present study aimed to investigate the global prevalence of stillbirth among fetuses resulting from twin pregnancies through a systematic review and meta-analysis. Methods: To identify relevant studies, we adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We searched databases including PubMed, Web of Science, Google Scholar, Scopus, Embase, and Science Direct using keywords such as “stillbirth,” “twin pregnancy,” “fetus,” and “prevalence” without applying any time constraints to the search. The quality of the articles was evaluated using the STROBE checklist. To ensure the reliability of our findings, we employed a random-effects model for analysis, and the heterogeneity of the studies was assessed using the I2 index. Data analysis was conducted using Version 2 of Comprehensive Meta-Analysis software. Results: In a review of 10 studies with a sample size of 627,797 people, our meta-analysis revealed a global prevalence of stillbirth among fetuses resulting from twin pregnancies, reported to be 1.4% (95% CI 0.9–2.1). Our study also showed that with increasing sample size and years of study, the global prevalence of stillbirth among fetuses resulting from twin pregnancies decreased (p < 0.05). The highest prevalence of stillbirth, 3.5 (95% CI 2.2–5.4), was reported in the monochorionic type. Conclusion: The occurrence of stillbirth in twin pregnancies is a significant health concern for countries worldwide. Identifying its prevalence and contributing factors can aid health planning and policy development.